CT findings, management and short‐term outcome of dogs with pyothorax: 101 cases (2010 – 2019). (12th July 2021) - Eiras‐Diaz, A.; Frykfors von Hekkel, A.; Hanot, E.; Stanzani, G.; Florey, J.; Miller, R.; Llabres‐Diaz, F.
Abstract : Objectives: To describe diagnosis, CT findings, management and short‐term outcome of a large population of canine pyothorax cases. Methods: Retrospective analysis of 101 canine pyothorax cases at two UK referral centres. Medical records and CT images were reviewed. Dogs were included if pre‐ and post‐contrast CT was performed within 48 hours of presentation. Results: CT abnormalities included pleural thickening (84.1%), pannus (67.3%), pneumothorax (61.4%), mediastinal effusion (28.7%), pulmonary (13.8%) and mediastinal (7.9%) abscessation, foreign body presence (7.9%), foreign body tracts (6.9%) and pneumonia (6.9%). Seventy‐one percent of dogs were managed surgically, of which 90.2% survived, and 29% were managed medically, of which 72.4% survived. Overall mortality was 14.8% and 86.6% of these dogs died within 48 hours of admission. All dogs with evidence of a foreign body on CT underwent surgery. Clinical significance: Mortality in our population was low and most dogs that died did so within 48 hours of hospitalisation, regardless of management type.